Bioluminescence (IntechOpen, 2023)
This book contains seven chapters on bioluminescence techniques and organisms. On the technical side, the four chapters presented the fluorescent markers of proteins and nanocrystals, imidazopyrazine-type luciferin that emits light when bound to human serum albumin, firefly luciferin that emits near-infrared light, and imaging technique for visualization of promoter activity in fruiting body formation of cellular slime molds Dictyostelium. On the organismal side, the three chapters presented recommendations for the commercial use of fireflies in urban areas from the perspective of conservation biology, the origin of luciferin by predation in marine luminescent organisms, and the ecology and behavior of luminescent organisms from sea to land, which will be of interest to both professionals and students.